An Ultrastrong and Highly Stretchable Polyurethane Elastomer Enabled by a Zipper‐Like Ring‐Sliding Effect - Shi, Chen‐Yu; Zhang, Qi; Yu, Cheng‐Yuan; Rao, Si‐Jia; Yang, Shun; Tian, He; Qu, Da‐Hui (Advanced materials (Weinheim), 2020)
Elastomers with excellent mechanical properties are in substantial demand for various applications, but there is always a tradeoff between their mechanical strength and stretchability. For example, partially replacing strong covalent crosslinking by weak sacrificial bonds can enhance the stretchability but also usually decreases the mechanical strength. To surmount this inherent tradeoff, a supramolecular strategy of introducing a zipper‐like sliding‐ring mechanism in a hydrogen‐bond‐crosslinked polyurethane network is proposed. A very small amount (0.5 mol%) of an external additive (pseudo[2]rotaxane crosslinker) can dramatically increase both the mechanical strength and elongation of this polyurethane network by nearly one order of magnitude. Based on the investigation of the relationship between molecular structure and mechanical properties, this enhancement is attributable to a unique molecular‐level zipper‐like ring‐sliding motion, which efficiently dissipates mechanical work in the solvent‐free network. This research not only provides a distinct and general strategy for the construction of high‐performance elastomers but also paves the way for the practical application of artificial molecular machines toward solvent‐free polyurethane networks. A molecular zipper elastomer—the combination of ring‐sliding effects and dense hydrogen‐bonding crystal domains in a dry polymer network—results in unexpectedly substantial improvements to the elastomer mechanical performance, including stretchability and strength. The mechanism is found to be the ring‐sliding motion against hydrogen‐bonding domains upon stretching, which effectively dissipates the input mechanical energy.